Translating Togay Murod: A Framework for Balanced Equivalence, Cultural Mediation, Stylistic Sensitivity, and Contextual Awareness - Isakova N.A; Nafasova G (Web of Scientist International Scientific Research Journal, 2026)
This study examines the theoretical foundations and practical strategies for translating the works of the contemporary Uzbek writer Togay Murod into international languages. The research establishes a framework combining formal, dynamic, and functional equivalence with cultural mediation and stylistic sensitivity. It analyzes specific lexical and grammatical challenges inherent in Murod’s culturally specific prose. The application of the proposed framework demonstrates that balancing linguistic fidelity with cultural nuance allows for a more accurate representation of the author’s literary artistry. Effective translation of Murod’s work requires a deep understanding of Uzbek cultural specificity and stylistic distinctiveness. This balanced approach ensures that the translations are resonant with an international readership while preserving the original’s tone.